Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Produk Fashion E-Commerce - Halimah Zahrah; Nazhara Azmi (Indo Publishing, 2026)
The rapid development of e-commerce in the fashion industry has intensified competition among brands, requiring companies to understand the factors influencing consumer purchase decisions. This study aims to analyze the effect of product quality and price on purchase decisions of fashion e-commerce products, specifically focusing on the Erigo brand. This research employs a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 138 respondents who are Management students at Universitas Muhammadiyah Bandung and have previously purchased Erigo products. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 27. The results indicate that product quality has a positive and significant effect on purchase decisions with a regression coefficient. Price also has a positive and significant effect on purchase decisions with a regression coefficient. Simultaneously, product quality and price significantly influence purchase decisions with a contribution, while the remaining variance is influenced by other factors outside this study. These findings suggest that improving product quality accompanied by appropriate pricing strategies can enhance consumer purchase decisions in the fashion e-commerce sector